MS-PBFT: A Master-Slave Multichain Consensus Mechanism Based on Pre-Broadcast and Threshold Signatures - Bohan Kang; Yunzhi Chen; Jianming Zhu (Tehnički Vjesnik, 2024)
This paper addresses scalability limitations in blockchain systems for supporting multi-asset transactions by proposing a master-slave multi-chain architecture. The underlying consensus protocol, called MS-PBFT, utilizes pre-broadcast and threshold signatures to reduce communication overhead. Experimental results demonstrate that MS-PBFT achieves substantially higher transaction throughput and lower latency compared to PBFT consensus, showcasing efficiency gains. This work provides a useful blockchain structure and consensus approach to enable classification of digital assets and concurrent processing across chains.